متطلبات تجسيد التسويق الابتكاري ودوره في تعزيز الميزة التنافسية للمؤسسة دراسة حالة مؤسسة اتصالات الجزائر بمستغانم - بوطلاعة, محمد; بن دبيش, نعيمة (جامعة الوادي - University of Eloued, 2018)
الملخص: تهدف هذه الدراسة إلى التعرف على دور التسويق الابتكاري في تعزيز الميزة التنافسية للمؤسسة، وذلك من خلال دراسة تطبيقية بمؤسسة اتصالات الجزائر –وحدة مستغانم، ولتحقيق أهداف الدراسة تم إعداد إستبانة لغرض جمع البيانات من أفراد عينة الدراسة، كما تم الاعتماد على برامج الحزمة الإحصائية للعلوم الاجتماعية (SPSS) لمعالجة البيانات. ولقد أظهرت النتائج وجود علاقة ذات دلالة إحصائية بين التسويق الابتكاري والميزة التنافسية للمؤسسة، كما أظهرت النتائج تفاوت تأثير المتغيرات المستقلة (الابتكار في: الخدمة، سعرها، ترويجها، وتوزيعها) على الميزة التنافسية. Abstract: The aim of this study is to identify the role of innovative marketing in enhancing the competitive advantage of the institution through an applied study in the Algerian Telecom Corporation – the Unit of Mostaganem, and to achieve the objectives of the study, we used a questionnaire for the purpose of collecting data from the sample of the study, and also relied on the statistical package program for the social sciences ( SPSS) to process the data. The results of the study showed the existence of an influential statistical relationship between marketing innovation and the competitive advantage of the institution. Moreover, the results showed that all independent variants (innovation in: service, price, promotion, and distribution) have a positive influence with different degrees of keeping competitive advantage.
Requirements for the embodiment of innovative marketing and its role in enhancing the competitive advantage of the corporation Case study of the Algerian Telecom Corporation in Mostaganem
مقال
Keywords: التسويق الابتكاري ; الميزة التنافسية ; اتصالات الجزائر –وحدة مستغانم